Solomon Islands : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2006)
Since the intervention of the Regional Assistance Mission to the Solomon Islands, growth has rebounded, and financial stability has been maintained. Fiscal discipline should be sustained, and a medium-term strategy developed taking into account looming pressures. The central bank's current exchange rate policy is appropriate, but requires vigilance. Financial system soundness should be strengthened by liquidating the development bank, and raising the profitability of the National Provident Fund. Structural reforms to encourage new private sector activities should be vigorously implemented.